In situ measurement of the strains within a mechanically loaded polygranular graphite. (January 2016) - Marrow, T.J.; Liu, D.; Barhli, S.M.; Saucedo Mora, L.; Vertyagina, Ye.; Collins, D.M.; Reinhard, C.; Kabra, S.; Flewitt, P.E.J.; Smith, D.J.
Abstract: Neutron diffraction and synchrotron X-ray diffraction and imaging have been applied to study, in situ, the mechanical response to tensile and bending loading of polygranular Gilsocarbon nuclear grade near-isotropic graphite (grade IM1-24). Digital image correlation of X-ray radiographs and digital volume correlation of tomographs allow measurement of bulk elastic moduli and examination of the heterogeneity of deformation in the microstructure. Both the neutron and X-ray studies show the application of tensile strain reduces the bulk elastic modulus. A permanent set is observed to develop with applied tensile strain. The elastic strains within the graphite crystals were measured by diffraction; a cross-correlation analysis method has been applied for greater speed, robustness and improved precision in the measurement of the change in basal plane separation distance. In compression, a linear relation is observed between the elastic strains in the graphite crystals and the applied strain. In tension, this relationship is non-linear. The results are discussed with respect to the distribution of elastic and inelastic strain within the graphite microstructure. It is deduced that the significant residual elastic strains in the as-manufactured graphite are relaxed by microcracking as tensile strain is applied.